Narrativas autobiográficas de humanização e afeto de uma profissional de apoio escolar - Silva, Ana Karolina (2025)
This dissertation describes my personal and professional journey as a school support worker, highlighting a three-month period of work with an adolescent with multiple disabilities at a school in the municipality of Uberlândia (MG). The study explores the possibilities and challenges encountered during this period, emphasizing five personalized pedagogical activities developed specifically for the student. The research is grounded in the theoretical contributions of Paulo Freire, focusing on his reflections on humanization and affection in the educational process. A narrative methodology is employed, valuing subjectivity and the uniqueness of lived experiences. This study details my life story, the work with a student with multiple disabilities, the daily routine of a school support professional, the pedagogical practices employed, and the strategies specifically adopted for the student in this dissertation. Furthermore, it examines the perceived achievements, both in the student's development and in the enhancement of my professional practices. Through this account, the aim is to offer a reflection on the role of affection, personalization, and the responsibility of teaching individuals with specific educational needs, contributing to the discussion on inclusive and humanized educational practices. Keywords: Autobiography, multiple disabilities, school.